Assessment of the efficiency of essential oils in the preservation of postharvest papaya in an antimicrobial packaging system - Espitia,Paula Judith Perez (2012)
Rot and damage caused by post-harvest phytopathogenic fungi affect fruit quality. Essential oils (EO) are considered as an alternative to fungicides. Postharvest diseases of fruits may also be controlled by the bagging approach and the use of antimicrobial packaging. Based on the beneficial properties of EO and the concepts of bagging and antimicrobial packaging, this study aimed to develop sachets containing EO to be used as part of an antimicrobial packaging system. The activities of oregano, cinnamon and lemon grass EO were evaluated testing the sachets in vitro against the phytopathogenic fungi Alternaria alternata, Fusarium semitectum, Lasiodiplodia theobromae and Rhizopus stolonifer. The effects of the sachets on the microbiological and physicochemical parameters of post-harvest papaya were also evaluated. Both pure and sachet-incorporated EO showed antifungal activity in vitro against all tested fungi. For papaya, sachets containing cinnamon, oregano and lemon grass showed a significant reduction in the growth of mesophilic aerobic bacteria, yeasts and mould, with the cinnamon sachet causing the greatest reduction in microorganisms at the end of the storage time. Physicochemical parameters of papaya, such as weight loss, colour, firmness, total soluble solids/titratable acidity ratio and pH were not significantly altered by the presence of EO sachets, thus not affecting the natural ripening process of the papaya.